(untitled) (Conferencea, 2023)
Currently, many mathematical packages have been created and are widely used. The most common of them are Maple, Matlab, Derive, Eureka, Mathematika, Maple packages. These packages are multi-functional packages. Today, the place and role of mathematical packages in the educational process is much more significant and effective. Formation of students’ skills and competencies in using mathematical packages is one of the main components of computer science. By making it easy to solve complex math problems, it takes the stress out of learning math and makes it fun and very simple. "MATLAB" package has an important place among the automation systems of mathematical calculations.